ANTHROPOTECHNICS AND THE ABSOLUTE IMPERATIVE. Issue 1 (2nd January 2021) - Roney, Patrick
Abstract: This essay attempts to interrogate the distinct character of Peter Sloterdijk's declaration of the absolute imperative that concludes his work, You Must Change Your Life, by contextualizing it within the development of his notion of anthropotechnics. In particular, the essays examine the claim that his is a new and unprecedented form of the absolute imperative that is alone able to address, in an effective way, the contemporary global crises that are confronting us now. The first sections trace out the ways in which this new imperative differs from previous forms of the imperative, including the categorical, the aesthetic, and the existential-ontological. The latter sections then discuss how the new form of the imperative is connected to Sloterdijk's radical attempt at a rethinking of the essence of the human as always already technological, which is the very project of anthropotechnics. This leads finally to a discussion of Sloterdijk's polemical engagement with Heidegger's question concerning technology, in which I trace out his attempt at a sweeping translation of Heidegger's notion of enframing [ Gestell ] into enhousing [ Gehäuse ] and the consequences thereof.